2021
DOI: 10.1186/s13027-021-00410-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the presence of Mycoplasma hyorhinis, Fusobacterium nucleatum, and Helicobacter pylori in biopsies of patients with gastric cancer

Abstract: Background Gastric cancer is the third leading cause of cancer-related deaths worldwide and has been associated with infections that may promote tumour progression. Accordingly, we analysed the presence of Mollicutes, Mycoplasma hyorhinis, Fusobacterium nucleatum and Helicobacter pylori in gastric cancer tissues and evaluated their correlation with clinicopathological factors. Methods Using a commercial kit, DNA were extracted from 120 gastric sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 75 publications
0
12
0
2
Order By: Relevance
“…Therefore, in this study, we focused on the analysis of F. nucleatum, a pathogenic bacterium found in the oral microbiota. Indeed, several studies have confirmed that this bacterium has a high prevalence in H. pylori ‐associated gastric cancer, which can increase the expression of gastric cancer‐associated bacteria through DNA alterations 48–50 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in this study, we focused on the analysis of F. nucleatum, a pathogenic bacterium found in the oral microbiota. Indeed, several studies have confirmed that this bacterium has a high prevalence in H. pylori ‐associated gastric cancer, which can increase the expression of gastric cancer‐associated bacteria through DNA alterations 48–50 …”
Section: Discussionmentioning
confidence: 99%
“…Annexin A2 is increased in multiple tumors and is associated with tumor grade and clinical outcome 31,32 . Recent studies have uncovered a relationship between ANXA2 and microbial infection 33,34 . For instance, ANXA2 contributes to human papilloma virus infection 35 and participates in HCV replication 35 .…”
Section: Discussionmentioning
confidence: 99%
“… 31 , 32 Recent studies have uncovered a relationship between ANXA2 and microbial infection. 33 , 34 For instance, ANXA2 contributes to human papilloma virus infection 35 and participates in HCV replication. 35 In addition, ANXA2 facilitates mycoplasma infection through its N‐terminal.…”
Section: Discussionmentioning
confidence: 99%
“…F. nucleatum was found to be positive in 19 samples (26.0%) of gastric cancer patients, while 1 sample (2.5%) was found to be positive in cancer-free patients. The prevalence of F. nucleatum was associated with 11-fold increase in the risk of developing gastric cancer, and was related with advanced age ( P =0.030) and large tumor size ( P =0.053) ( 53 ). According to the profiles of gastric epithelium-associated microbiota in patients with gastritis, intestinal metaplasia, and gastric cancer, it was indicated that gastric microenvironment was frequently enriched with Clostridium and Fusobacterium in gastric cancer patients.…”
Section: F Nucleatum In Gastric Cancermentioning
confidence: 99%